Whole genome sequencing, characterization and analysis of coronene degrading bacterial strain Halomonas elongata - Thasneema Rafic; Mohammed Alarawi; Omer Salem Alkhnbashi; Assad Al-Thukair; Ajibola H. Okeyode; Karthikeyan G; Alexis Nzila (PLoS ONE, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are persistent environmental pollutants with significant ecological and health risks. Among them, coronene, a high molecular weight PAH, is particularly resistant to biodegradation due to its complex structure. This study characterizes a halophilic bacterial strain, initially identified as Halomonas caseinilytica and later reclassified as Halomonas elongata , capable of utilizing coronene as its sole carbon source under high salinity (10% NaCl). Whole genome sequencing using Oxford Nanopore technology (ONT) revealed 4,308 predicted genes, including those linked to hydrocarbon metabolism, stress adaptation, and secondary metabolite biosynthesis. Pathway analysis identified genes associated with xenobiotic degradation, although no canonical coronene specific degradative enzymes were identified, implying that the bacteria may be utilising an alternative or novel pathway. Comparative annotation uncovered operons and enzymes relevant to aromatic compound breakdown. Notably, the presence of ectoine biosynthesis genes suggests a robust osmoadaptation system. Features such as mobile genetic elements and horizontal gene transfer events were also investigated. These findings expand current knowledge on PAH-degrading halophiles and highlight the potential of H. elongata in bioremediation of saline and hypersaline environments contaminated with complex hydrocarbons. The study also emphasises the potential of long read sequencing technologies in environmental genomics and bioremediation.